PELATIHAN PENGELOLAAN DAYA TARIK WISATA ALAM SUMBERINGIN DI DESA WRINGINSONGO, KECAMATAN TUMPANG - Isnaini Nur Safitri; Tiara Estu Amanda; Asa Wisesa Betari; Ardian Wahyu Setiawan; Mariana Ulfah Hoesny (P3M Politeknik Negeri Malang, 2024)
This community service is aimed at accommodating the needs of the management of the Sumberingin natural tourist attraction in improving the ability to manage natural tourist attractions and tourism potential in the Wringinsongo village area by involving tourism business actors (travel agents) to increase tourist visits, both local and foreign. Participants in this training are tourist attraction managers, especially Sumberingin tourist attraction managers and Wringinsongo village managers, Tumpang District, Malang Regency. This activity is expected to improve the quality of human resources for tourist attraction managers by increasing the ability to manage tourist attractions, which will then be implemented as an effort to increase local and foreign tourist visits. This activity was carried out in some stages, namely planning (to find out the number of participants who were involved and the materials needed for the training), coordination with the related parties (representative of partner village members, travel agent, and tour guide) to ensure the plans made are in accordance with the needs, preparation of Focused Group Discussion (FGD) materials, survey to the exact location in the partner village to ensure the prepared materials are suitable with the condition of the village, doing FGD with the, and evaluation which is giving questionnaires to the participants regarding the implementation and materials.